Active Control of Contact Force for a Pantograph-Catenary System - Jiqiang Wang (Shock and Vibration)
The performance of the high speed trains depends critically on the quality of the contact in the pantograph-catenary interaction. Maintaining a constant contact force needs taking special measures and one of the methods is to utilize active control to optimize the contact force. A number of active control methods have been proposed in the past decade. However, the primary objective of these methods has been to reduce the variation of the contact force in the pantograph-catenary system, ignoring the effects of locomotive vibrations on pantograph-catenary dynamics. Motivated by the problems in active control of vibration in large scale structures, the author has developed a geometric framework specifically targeting the remote vibration suppression problem based only on local control action. It is the intention of the paper to demonstrate its potential in the active control of the pantograph-catenary interaction, aiming to minimize the variation of the contact force while simultaneously suppressing the vibration disturbance from the train. A numerical study is provided through the application to a simplified pantograph-catenary model.